(3MQeI GdZdjGf aj TgQ QeVGfs - (3GdcQHGSj, eMeO EHQGgje Hf eMeO MSf, J (B1260 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B...(3hdG jSYfj EdG Cbd eG jJVM Hg GdHjGf (B... (3hCfg eG jdRe HJYeOg GdbVGA hGdcaGQI HGdMLI hGdHQgGf (B... (3afbhd jJhba GdJMbjb Ydi LeY cdeGJ Gbhe aj GdZHGQ hGdONGf hGdJcde ajg MJi jXgQ aGJhjge aj GdebGe (B...s
(3BNQgG (B:s
... (3adeG QCi Pdc GdSdWGf Cf Pdc GdNQhL dG jfaY bQQ Ydjg ef eGd GdGNQGL eGdG YXjeG Hbi Edi YUQfG bUO Hg JYLjR GdfGS Yf GdJLGQI (B...(3ef ebGHM GdCaYGd GdOfjhjI JeJs
(3HBNQgG aGFOI HGdaGQSjI HJGQjN (B1 (3QLH (B1258 (3g`s
(3JHUQI GdYfhGf (B:s
(3aj eYQV GdcdGe Yf cTa GdChgGe ddfhQj GdWHQSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B5\305s
(3GdPQjYI (B18- 16 (484)s
Keywords: (3abg GdePGgH GdCNQis